Moral Construction of the Message Transformation Process in the Scene from the Film 'Budi Pekerti' - Vera Alfina Syifa; Ika Amelia; Khaerudin Imawan (CV. Media Digital Publikasi Indonesia, 2025)
In today's era, the dissemination of information often experiences distortion due to external factors or interpretations from social media. This study aims to explain the development of information dissemination values using the film “Budi Pekerti.” Through the lens of social construction theory proposed by Peter L. Berger and Thomas Luckmann, this method identifies three forms of reality: externalization, objectification, and internalization. This study falls under qualitative research with a descriptive approach. The film illustrates how moral values are socially constructed and perceived in the current media context, particularly social media. This highlights the implications of moral relativism, where moral beliefs are seen as relative to individual or social perspectives. The narrative follows the character of Mrs. Prani, a Guidance Counselor, whose actions and public reactions highlight the complexity of moral judgment in the digital age. The study reveals that the lack of moral awareness in message transformation is exacerbated by a lack of mutual respect and honesty, leading to negative consequences for those involved. Ultimately, the film serves as a medium to convey important moral messages and critique the role of media in shaping public perception and moral standards.